2022
DOI: 10.1055/a-1987-3205
|View full text |Cite
|
Sign up to set email alerts
|

Exposure and Response Prevention for Children and Adolescents with Tourette Syndrome Delivered via Web-Based Videoconference versus Face-to-Face Method

Abstract: Chronic tic disorders, such as Tourette Syndrome, are characterized by motor and vocal tics. Tics present a considerable burden for some patients, and therefore effective treatment is important. One evidence-based treatment option is a behavioral therapy called Exposure and Response Prevention (ERP). Despite its effectiveness, access to ERP remains limited due to a lack of treatment sites. Web-based videoconferences can connect patients at home with a therapist located in the hospital, allowing for treatment d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
(80 reference statements)
0
4
0
Order By: Relevance
“…In this study by Sørensen and colleagues ( Sørensen et al . 2023a , 2023b ), 116 youth received ERP (either face-to-face [n = 72] or via videoconference [n = 44]) and were followed up one-year post-treatment. The study showed significant short- and long-term tic severity reductions (YGTSS-TTS) in both groups, with no significant between-group differences.…”
Section: Resultsmentioning
confidence: 99%
“…In this study by Sørensen and colleagues ( Sørensen et al . 2023a , 2023b ), 116 youth received ERP (either face-to-face [n = 72] or via videoconference [n = 44]) and were followed up one-year post-treatment. The study showed significant short- and long-term tic severity reductions (YGTSS-TTS) in both groups, with no significant between-group differences.…”
Section: Resultsmentioning
confidence: 99%
“…Both treatments are typically delivered in person, and thus, their availability is limited . To make BT more accessible, several studies have investigated ways to deliver BT remotely . In a large UK randomized clinical trial (RCT)—the Online Remote Behavioural Intervention for Tics (ORBIT) trial—224 young individuals with TS or CTD were randomized to 1 of two 10-week therapist-supported, internet-delivered interventions: ERP and psychoeducation.…”
Section: Introductionmentioning
confidence: 88%
“… 6 , 7 To make BT more accessible, several studies have investigated ways to deliver BT remotely. 8 , 9 , 10 , 11 In a large UK randomized clinical trial (RCT)—the Online Remote Behavioural Intervention for Tics (ORBIT) trial 12 —224 young individuals with TS or CTD were randomized to 1 of two 10-week therapist-supported, internet-delivered interventions: ERP and psychoeducation. At the primary end point (posttreatment), internet-delivered ERP was superior to psychoeducation in reducing tic severity, requiring only minimal therapist resources.…”
Section: Introductionmentioning
confidence: 99%
“…Further information about the web-based videoconferencing approach is described in another article by the same author group. 31 In the ERP treatment sessions, the patients systematically learned to suppress their tics for a prolonged period. If a tic occurred, the patient was asked to start over again, encouraged by the therapist to improve the performance.…”
Section: Treatmentmentioning
confidence: 99%